The Collapse of Real Socialism in Eastern Europe versus the Overthrow of the Spanish Colonial Empire in Latin America: An Attempt at Comparative Analysis - Brzechczyn, Krzysztof (Centre of Advanced Study, University of Allahabad, India, 2004)
After the collapse of real socialism, Fukuyama proclaimed the 'end of history' and the triumph of liberal democracy. However, history of Latin America shows that the democracy is a very fragile political system. Its stability depends on the social contexts in which it exists. Therefore, it is worth to ask about future of democracy in Eastern Europe. Based on Nowak's non-Marxian historical materialism, author distinquishes class societies where separate classes of rulers, owners and priests exist and supra class societies where class divisions are cumulated. This distinction allows for answering this question in the following manner. The durability of democracy depends on the relationship between social classes. The more these relations approximate the class society, the more stable the democracy is. The more a given society is distant form the class society, the more the democratic system is distorted. This thesis is ilustrated by comparative analysis of social transformation in Mexico and Poland.
Keywords: Non-Marxian historical materialism; Transformation; Poland; Mexico